Accurate Control Multiple Active Sites of Carbonaceous Anode for High Performance Sodium Storage: Insights into Capacitive Contribution Mechanism. Issue 7 (10th January 2020) - Lu, Yun; Liang, Jianing; Hu, Yezhou; Liu, Yi; Chen, Ke; Deng, Shaofeng; Wang, Deli
Abstract: Heteroatom doping is widely recognized as an appealing strategy to break the capacitance limitation of carbonaceous materials toward sodium storage. However, the concrete effects, especially for heteroatomic phase transformation, during the sodium storage reaction remain a confusing topic. Here, a novel hypercrosslinked polymerization approach is demonstrated to fabricate pyrrole/thiophene hypercrosslinked microporous copolymer and further give porous carbonaceous materials with accurately regulated N/S dual doping corresponding to starting feeding ratios. Significantly, the N doping contributes to the conductivity and surface wettability, while the S doping is bridged to build stable active sites, which can be electrochemically converted into mercaptan anions via faraday reaction and further enhancing reversible capacities. Meanwhile, the abundant S doping can also conduce to the expanded interlayer spacing to shorten the ions diffusion distance, thus optimizing the reaction kinetic. As a result, the N0.2 S0.8 ‐micro‐dominant porous carbon delivers the highest reversible capacity of 521 mAh g −1 at 100 mA g −1 and excellent cyclic stability over 2000 cycles at 2000 mA g −1 with a capacity decay of 0.0145 mAh g −1 per cycle. This work is anticipated to provide an in‐depth understanding of capacitance contribution and illuminate the heteroatomic phase transformation during sodium storage reactions for doping carbonaceous anodes. Abstract : Sodium storage mechanisms consist of three parts: i) the considerable faraday behavior, ii) the adsorption pore filling mechanism, and iii) the ion intercalation behavior. This work provides an in‐depth understanding of capacitance contribution, illuminates the heteroatomic phase transformation, and breaks the capacitance limitation of carbonaceous anodes toward sodium storage.